Multicultural Politics of Recognition and Postcolonial Citizenship - syamsu, suhardiman (Politics and Humanism, 2022)
One of the current debates in the social sciences is related to the linkage between aspects of ethnicity, race and cultural diversity, related to citizenship, the issue of inclusiveness and political community. This debate is inseparable from the tendency of the liberal democratic system today which currently dominates the dynamics of social science thinking. This debate is related to fact that these various aspects are often encountered in an understanding that seems to tend to be dichotomous. This condition makes discussion about these aspects encourage desire to examine them in various theories and various frameworks of thought. One perspective that is offered to examine the debate is structuralism which is then linked to normative theories of multiculturalism and is accompanied by the presence of postcolonial criticism of ethnic and racial hierarchies in politics as discussed very well in this book by Rachel Busbridge.